Research streams in corporate social responsibility literature: a bibliometric analysis - Ilka Marie Frerichs; Thorsten Teichert (Management Review Quarterly, 2021)
Corporate social responsibility (CSR) research is heterogeneous and still fragmented. In its interdisciplinary setting, researchers focus on different CSR aspects, secondary concepts and themes. The lack of a unifying paradigm indicates that the CSR literature should be summarized and classified. This study's systematic overview of CSR research provides such a classification. Previous conceptualizations of CSR research mapped the literature from individual authors' perspective, rendering different and partly inconsistent classifications. Using bibliometric methods, this paper offers an objective overview. We analyze the references of 1902 CSR journal articles by bibliometric techniques as (co-)citation, core/periphery, factor, and network analyses. By doing that, we provide an overview of the CSR research core, identify different research streams, describe their main publications' topics and recent developments, and make suggestions to inspire future research in and across research streams. Our results show the increased relevance of formerly niche research streams, such as employee-oriented CSR research, or research on consumer skepticism. Among others, process-oriented and micro-level research, critical approaches, and mergers between themes from various research fields offer a wide scope for further research.
Keywords: 650; Corporate social responsibility; CSR conceptualization; Research streams; Bibliometrics; Co-citation analysis; M140